PENGARUH DEBT TO EQUITY RATIO (DER) DAN RETURN ON ASSETS (ROA) TERHADAP HARGA SAHAM BANK BUSN YANG TERDAFTAR PADA BURSA EFEK INDONESIA (BEI) PERIODE 2017-2021 - Nurul Husna; Noor Hidayati; Nurul Wahyuni; Novia Nour Halisa (Smart Business Journal (SBJ), 2023)
This study aims to test how much influence DER and ROA have on share prices partially and simultaneously. In this case uses quantitative research with explanatory research. The populations of this research is the financial reports of BUSN banks which are in IDX., the sample used is the financial reports of BUSN banks which are listed IDX and continuously report or publish their financial reports in the 2017-2021 period with using sampling techniques. used was purposive. The data used type is secondary data in the form of company annual reports from the IDX. The techniques used is through documentation. The data analysis technique in this study uses multiple liner analysis. The final results showed that the DER partially had a significancy effect on stock prices with a sig value of 0.001 under 0.05. ROA partially has a significancy effect on stock prices with a sig value of 0.001 under 0.5. Then the DER and Return On Assets (ROA) simultaneously have a significant effect on stock prices with a sig value of 0.001 under 0.5.